153 NUMARALI EDİRNE ŞER'İYYE SİCİLİ H.1164 - 1170 / M.1750 - 1756 - ŞENGÜR, SABİHA (Fırat Üniveristesi, 2007)
Bu tez, 153 Numarah Edime Ser'iyye Sicilli'dir. Sicili, Hicri1164-1170 / Miladi 1750-1756 yl1lan arasml kapsamaktadu. Bu donemde Edime, Rumili Eyaletine bagh merkezi kaza statiisiinde oldugunu tespit ettik. Bu tezinizde Osmanh adliye te~kilatl ve ~er'iyye sicilleri'nin nitelikleri hakkmda bilgiler verdikten sorna sicillerin ihtiva ettigi belgelerin ozetlerini transkripsiyonunu verdik. Son olarak da ~er'iyye sicillerine dayanarak Edime'nin iktisadi, i9timai, siyasi ve idari yaplsl hakkmda geneI bir degerlendirme yaptlk. Edime Kazasl'mn 0 donemde 4 nahiyesi ile ~ehir merkezine bagh 29 koyiinii tespit ettik. Sicil'lerde vakIf ile ilgili belgenin yamnda tereke defteride bulunmaktadu. Edime ve civannda vaklf akarlarmm yangm veya ba~ka bir sebeble ylkl1dlgml ve tamir edildigini aynca. Bila-varis fevt olanlann terekelerinin beytii'-mal tarafmdan el kondugunu gordiik. Bugiin Edime'de me~hur olan siipiirge, boya ve tahta i~lemeciligi ile ilgili tasarruf e~yalanndan bahsedildigini sicillerde mii~ahede etmekteyiz. Edime KazaSl ve dahilinde orfi gorevlilerin reaya zulm ve teaddide bulundugunu da belgelerden ogreniyoruz.

This thesis is 1 53 number ofthe "Edirne Ser'iyye Records" and the record includes the years between 1 164-1 170 B.C.l1750-1756 A.D.We established that Edirne was in the central "kaza" status and yas subject to the Province of Rumeli. In this our thesis, we presented the transcription and the absracts of the documents that the records contain after we gave datas concerning the charctericts ofthe ~er'iyye records and Ottoman justice organization. Lastly, we evaluated the economic, ethnographic, political ve administrative structme ofEdime oniy on the basis ofthe ~er'iyye records. We determined that Edirne "Kaza" had 4 "mlhiye" and 29 villages which were subject to the "kaza". There are also inventories of the estates in addition to the documents relevant to wakfin the records. We observe that the rental properties ofwaqfvere in ruins on account of another reasons or fire also confiscated to the estate's inventories ofpersons who died without heir by "Beytit' 1 -mal". We observe that phrases pertaining to broom sellers, painters, soapers such as "Sabuncular Hani, Boyahne, Siipiirgeciler Hm" and also the board work which become famous in Edirne today vere mentioned in records. We learn from the records that the martial managers behaved cruelty to raya in Edirne Kaza and in the vicinitv of it.
Edirne şer'iyye records no 153
Keywords: Tarih